স্বাধীনতার মুখ - ত্রিপাঠী, অমলেশ, ১৯২১- (কলকাতা : আনন্দ পাবলিশার্স, 1998)
Historical articles chiefly on 20th century India.
গ্রন্থপঞ্জিগত নির্দেশিকা ও নির্ঘণ্ট অন্তর্ভুক্ত।
Donated By Akbar Ali Khan
In Bengali; includes passages in English.
Keywords: India -- History -- 20th century; India -- History